Formation CMOS Schemes on GaAs with Self-Aligned Nitride and Silicide Gates - Novosjadly, S.P.; Terletsky, A.I.; Fryk, O.B. (Physics and Chemistry of Solid State, 2015)
Advanced integrated logic circuits on GaAs are mainly based on the using of n-channel field-effect transistors with gate Schottky (MESFET). To create the complementary MESFET integrated circuits the main problem is quite small Schottky barrier height (< 0,5 eV) on p-type gallium arsenide. One way to solve this problem is to use a nitride or silicide tungsten compounds to form gates given the thickness and composition. This paper highlights the features of the formation of complementary high-speed logic circuits on the p-GaAs with self-aligned gate based on nitride or silicide of tungsten obtained by reduced pressure horizontal reactor "Izotron 4" and of RF magnetron sputtering equipment "Oratorio-5." This technology can also be used to form a Schottky contact to n- channel MESFET. Since the manufacturing process of MESFET self-aligned gate provides using refractory gate material as a mask for the multiply ion implantation, the Schottky contact must withstand subsequent high-temperature heat treatment required to activate implanted impurities. In this connection, the action of high-temperature photonic and resistive heating on the barrier height of Schottky contact formed by nitride (silicide) tungsten (WNx, WSix) GaAs was also studied.